Superior‐Selective and Complete Recycling of Trace Precious Metals From Wastewater by Magnetic Trilayer Carbon‐Aerogels - Jianzheng Yang; Yan Zhou; Shang Du; Bing Wu; Jianying Zhang; Shanjun Song; Tao Zhou; Jinming Zhang (Advanced Science)
Abstract It is a considerable challenge to selectively recycle precious metals from industrial wastewater and natural waters. Herein, carbon aerogels embedded with magnetic Fe@FeS@C nanoparticles (CFeS aerogels) were constructed from natural carrageenan. The unique redox potential of FeS, coupled with the barrier effect and the electron conduction property of the carbon layer, made the Fe@FeS@C nanoparticles exhibited the ultra‐high ion selectivity. The resultant CFeS aerogels can selectively adsorb and reduce trace Au(III), Ag(I), and Pd(II) ions at ppb level in an aqueous solution with 29 coexisting cations. Even if the concentration of competing metal ions is 100‐fold higher than those of the precious metal ions, the selectivity for Au(III), Ag(I), and Pd(II) ions remained above 99.2%. Moreover, the 3D carbon network immobilizing the Fe@FeS@C nanoparticles prevented the aggregation and detachment of the recycled precious metals, thereby enhancing the adsorption rate and capacity. CFeS aerogels rapidly achieved adsorption equilibrium for Au(III), Ag(I), and Pd(II) ions in 5–10 min, and have the saturated adsorption capacities of 321.2 mg·g−1, 150.6 mg·g−1, and 70.1 mg·g−1, respectively. Such aerogels with ultra‐high selectivity, high efficiency, and easy separation provided a practical strategy for the enrichment and recovery of the precious metals.